2018
DOI: 10.3390/ijerph15051040
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk Assessment of Toxic Elements in Farmland Topsoil with Source Identification in Jilin Province, China

Abstract: The presence of toxic elements in agricultural soils from anthropogenic activities is a potential threat to human health through the food chain. In this study, the concentration of toxic elements in 122 agricultural topsoil composite samples were determined in order to study the current status, identify their sources and assess the level of pollution and human health risk. The results showed that the mean concentrations of Zn, Cu, Pb, Cd, Hg and As in the farmland topsoil were 21.72, 15.09, 36.08, 0.2451, 0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…However, unlike these studies, Kortei et al [74] showed that geophagic clays consumed by pregnant women at Ho in Ghana had HI values greater 1. [46,48,73]. These data agree with findings by Nkansah et al [22], who reported HI values in geophagic white clays from Kumasi Metropolis (Ghana) to be less than 1.…”
Section: Health Risk Assessmentsupporting
confidence: 90%
See 2 more Smart Citations
“…However, unlike these studies, Kortei et al [74] showed that geophagic clays consumed by pregnant women at Ho in Ghana had HI values greater 1. [46,48,73]. These data agree with findings by Nkansah et al [22], who reported HI values in geophagic white clays from Kumasi Metropolis (Ghana) to be less than 1.…”
Section: Health Risk Assessmentsupporting
confidence: 90%
“…The HI values were all less than 1, with means of 7.31 × 10 −5 , 6.73 × 10 −3 , 5.10 × 10 −1 , 1.2 × 10 −2 , 2.12 × 10 −2 , 1.15 × 10 −1 and 4.16 × 10 −3 for Fe, Co, Cr, Cu, Ni, Pb and Zn, respectively for children; and 8.3 × 10 −6 , 7.69 × 10 −4 , 6.26 × 10 −2 , 1.45 × 10 −3 , 2.56 × 10 −3 , 1.33 × 10 −2 and 4.79 × 10 −4 for Fe, Co, Cr, Cu, Ni, Pb and Zn, respectively, for adults. Hence, exposure to these metals would not cause a health risk to geophagists [46,48,73]. These data agree with findings by Nkansah et al [22], who reported HI values in geophagic white clays from Kumasi Metropolis (Ghana) to be less than 1.…”
Section: Health Risk Assessmentsupporting
confidence: 89%
See 1 more Smart Citation
“…The SD is highly correlated with the average concentration of metals, and the CV reflects their distribution. The SDs of Al, Fe, K, Na, Mg and Ti were large; and the metals were mainly derived from parent materials of the soil, indicating that these six metals were mainly derived from highly heterogeneous environments [55,56]. The CVs ranged from 6.16% to 174.19%; within this range, the CVs of Na, Mg, Cu, Pb, Zn, Cr, Ni, Ba, Co, As, Sn and Sr were greater than 50%, indicating that these metals are distributed variably or non-homogeneously in space [51].…”
Section: Resultsmentioning
confidence: 99%
“…Cr and Ni in the first principal component (PC1) was demonstrated to be derived from parent material and lithogenic sources in many studies [8,21,46]. However, as opposed to other studies [3,5,15,47], Cu in this study was not deemed to have an anthropogenic source; our results are consistent with those of Tian et al [48]. The results of FA showed that Cu did not belong to the second principal component (PC2) but was a group with Cr and Ni in PC1.…”
Section: Pc1: Cr Cu Nimentioning
confidence: 98%